Democracy, Investment and Economic Growth - Zouhaier, Hadhek; Karim, Kefi Mohamed (International Journal of Economics and Financial Issues, 2012)
The main purpose of this paper is to identify the relationship between democracy, investment and economic growth for a sample of 11 countries from the MENA region during the period 2000-2009, by using a dynamic panel data model. The democracy’ effect on the contribution of investment to economic growth has been the subject of a second empirical study within the framework of this research paper. The main outcomes drawn by these two empirical tests prove that there is a significant link between on the one hand the democracy and investment and on the other hand between civil liberties and economic growth. The outcomes also highlight a positive interaction between political rights and investment. Keywords: Political rights; Civil liberties; Investment; Economic growth; Dynamic panel JEL Classifications: O43; O47; C23